Effect of hydrophobically modified extracted starch nanocrystal on the properties of LDPE/ thermoplastic starch (TPS)/PE‐g‐MA nanocomposite. Issue 2 (5th August 2021) - Moazzami Goudarzi, Zahra; Behzad, Tayebeh; Sheykhzadeh, Aram
Abstract: In the current study, the key role of incorporation of starch nanocrystals (SNC) and modified acetylated starch nanocrystals (ASNC) on mechanical, physical, and biological properties of low‐density polyethylene/thermoplastic starch/polyethylene‐grafted‐maleic anhydride (LDPE/TPS/PE‐g‐MA) blend was individually investigated. To achieve this, SNC was successfully extracted from waxy maize starch by chemical treatment utilizing acid hydrolysis. The results of solubility of the modified specimens showed that the hydrophilicity of ASNC was well reduced by dispersion enhancement in non‐polar solvents, which was also proved by increasing considerably the contact angle, after modification, 37.9° ± 3.5° to 59.9° ± 3.1°. It was noticed that the mechanical properties of the ASNC nanocomposites were significantly affected by the filler type and content. Furthermore, by adding 3.0 wt% ASNC (3ASNC), the ultimate tensile strength of the nanocomposite was considerably enhanced from 9.0 ± 0.1 to 12.0 ± 0.3 MPa; it may be due to homogeneous dispersion of the ASNC. Moreover, the water absorption capacity was remarkably enhanced from 0.1% for the pure polymer, low‐density polyethylene (LDPE), to 1.9% for modified nanocomposite (3.0 wt% ASNC) and 4.1% for unmodified nanocomposite (5 wt% SNC). In addition, the degradation rate of 3ASNC nanocomposite was improved by 1% compared with LDPE. In conclusion, LDPE/TPS/PE‐g‐MA nanocomposite reinforced by ASNC shows excellent potential as a promising candidate for polyethylene packaging applications, thanks to the combination of biodegradability and superior mechanical properties. Abstract : Preparation steps of LDPE/TPS/SNC nanocomposites: (a) Isolation of SNC, (b) Surface modification of SNC, (c) Preparation of TPS, and (d) Manufacturing of LDPE/TPS nanocomposite.